Effect Of Vetiver Essential Oil In 10% And 30% Concentration To The Cortisol Hormones Of Stressor-Induced Rats - Willianto, Vincentius Michael; Suyono, Handi; Jong, F.X Himawan H. (JOURNAL OF WIDYA MEDIKA JUNIOR, 2020)
Background: The number of people with mental health problems is still high in the world, especially depression. This incident is triggered by the stress of each individual on anongoing basis and failure to adapt. Stress regulation is a preventive measure to preventdepression in individuals. Currently, there are many developing uses of essential oils as antistress relaxation therapy. Vetiver essential oil is believed to reduce stress levels. Purpose: This study aimed to determine the effect of using vetiver essential oil with different concentrations and administration periods on changes in cortisol levels. Methods: This study used Rattus norvegicus experimental animals with the Forced Swim Test (FST) as a stressor. Vetiver essential oil concentrations of 10% and 30% were administered with the essential oil preparation given after giving stressor. Stress level in experimental animals was measured from the hormone cortisol in the blood. The method of measuring cortisol in experimental animals was carried out using the Enzyme-Linked Immuno Sorbent Assay (ELISA) method. Results: This study obtained significant results from the Kruskal Wallis statistical test ondecreasing cortisol levels in experimental animals by administering vetiver essential oil with10% concentration. Changes in the cortisol hormone in experimental animals and cortisollevels were not affected by the length of time of administration.